Data networks : routing, security, and performance optimization - Kenyon, Tony, 1960- (Digital Press, 2002)
Data Networks builds on the foundation laid in Kenyon's first book, High-Performance Data Network Design, with expanded coverage of routing, security, multicasting, and advanced design topics such as performance optimization and fault tolerance. Kenyon provides strategies for overcoming some of the most challenging problems in network design and management. He provides clear, specific solutions for day-to-day problems facing network designers and IT managers. In this book, you will find optimization advice from an experienced practitioner that you can put to work in your own system. As security and network performance become more and more critical to a company's success, the system administrator's job becomes even more difficult. Use the principles, tips, and techniques Kenyon offers here to enhance and protect the flow of data within your enterprise. Covers Addressing, Routing, Multicasting, and Quality of Service (QoS) design for enterprise network design. Extensive coverage on relevant Security Technologies and Virtual Private Network (VPN) implementation Provides advanced coverage on Risk Assessment, Availability Analysis, Fault Tolerance, Disaster Recovery, and Network Optimization.